Testing for Facioscapulohumeral Muscular Dystrophy with Optical Genome Mapping. Issue 1 (17th January 2023) - Koppikar, Pratik; Shenoy, Suresh; Guruju, Naga; Hegde, Madhuri
Abstract: The introduction of optical genome mapping has improved time constraints and a lack of specificity from previous methodologies when performing genome‐wide analyses of samples. Optical genome mapping allows for the detection of structural variations, aberrations, and functionality traits from a single stained molecule of DNA. Though the preparation time is increased compared to previously utilized visualization techniques, optical genome mapping significantly reduces the time needed for analysis. Specifically, individual disease pipelines have been developed to rapidly analyze prepared samples. One of these diseases, Facioscapulohumeral Muscular Dystrophy (FSHD), is detected through quantification of the D4Z4 repeat array on chromosome 4q35. Optical genome mapping, with the ability to enumerate the repeats of the D4Z4 array, has demonstrated the capability to precisely diagnose FSHD. In this protocol, the preparation of samples and subsequent loading and analysis in an optical genome mapping system is discussed for the detection and analysis of FSHD. These methods should prove highly useful in FSHD analyses and beyond with the development of further disease analysis pipelines within the instrument. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : Genomic DNA isolation, labeling, and staining Basic Protocol 2 : Mapping and analysis with the Bionano Saphyr® system